Erratum: HLAVÁČ, P. (2012) Contribution to the knowledge of the tribe Mastigerina (Coleoptera: Staphylinidae: Pselaphinae, Clavigeritae), with a description of a new genus from Borneo. Zootaxa, 3070, 51–59. - Hlaváč, P. (Zootaxa, 2012)
(Erratum)